Analisis Pelaksanaan Monitoring Terhadap Pembiayaan Murabahah Di BPRS Patriot Bekasi - Fauziyyah, Nur; Isfandayani, Isfandayani; Mardiah, Siti (At-Tamwil: Journal of Islamic Economics and Finance, 2023)
The BPRS is one of the islamic finansial institutions that has positive development in Indonesia. BPRS activities are not much different from Sharia Commercial Banks, one of which is distributing financing. The most widely used financing for BPRS in Indonesia is murabahah financing. With the amount of murabahah financing carried out, BPRS must monitor so the implementation of financing is in accordance with the sharia principles, in accordance with the agreement, dan to keep the murabahah financing provided in a good condition. This study aims to determine the methods for enforcing murabahah financing at BPRS Patriot Bekasi, financing monitoring procedures for murabahah financing at BPRS Patriot Bekasi, and analyzing the monitoring implementation of murabahah financing at BPRS Patriot Bekasi. This study uses a qualitative research. The data sources used are primary data and secondary data, with data collection techniques through interviews, library research, and documentation. Data analysis techniques used in this study, are data reduction, facts presentation, and drawing conclusions. The results of the study is indicate that BPRS Patriot Bekasi adheres to the 5C principle inside the implementation of murabahah financing. The procedure for monitoring of murabahah financing at BPRS Patriot Bekasi is corresponding with the theory but with different name, that is On Site Monitoring and Off Site Monitoring.